An experimental intraradicular biofilm model in the pig for evaluating irrigation techniques - Toshinori Tanaka; Yoshio Yahata; Keisuke Handa; Suresh V. Venkataiah; Mary M. Njuguna; Masafumi Kanehira; Tatsuya Hasegawa; Yuichiro Noiri; Masahiro Saito (BMC, 2021)
Abstract Background We established an in vivo intraradicular biofilm model of apical periodontitis in pigs in which we compared the efficacy of different irrigant activation techniques for biofilm removal. Methods Twenty roots from the deciduous mandibular second premolar of 5 male pigs were used. After pulpectomy, canals were left open for 2 weeks and then sealed for 4 weeks to enable the development of an intracanal biofilm. The intraradicular biofilms was evaluated using SEM and bacterial 16S rRNA gene-sequencing. To investigate the efficacy of biofilm removal, root canal irrigations were performed using conventional needle, passive ultrasonic, subsonic, or laser-activated irrigation. Real-time PCR was conducted to quantitate the remaining biofilm components. Statistical analysis was performed using ANOVA followed by a Tukey kramer post-hoc test with α = 0.05. Results The pulp exposure model was effective in inducing apical periodontitis and SEM analysis revealed a multi-layer biofilm formation inside the root canal. 16S rRNA sequence analysis identified Firmicutes, Bacteroidetes, and Fusobacteria as the predominant bacterial phyla components, which is similar to the microbiome profile seen in humans. None of the tested irrigation techniques completely eradicated the biofilm components from the root canal, but the subsonic and laser-activated irrigation methods produced the lowest bacterial counts (p < 0.05). Conclusions An experimental intraradicular biofilm model has been successfully established in pigs. Within the limitations of the study, subsonic or laser-activated irrigation demonstrated the best biofilm removal results in the pig system.